Sistem Penyusunan Laporan Keuangan Berdasarkan Invoice pada Pt. Abc - Nazhiifah Huwaida Nisa; Ulfa Puspa Wanti Widodo (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of collecting invoices at PT. ABC is to ensure that all transactions are well documented and to ensure the completeness of transaction data for the purposes of financial recording and reporting. The use of invoices in preparing financial reports is the main basis that must be used at PT. ABC. Invoices allow companies to monitor and manage transactions more effectively, as well as facilitate the accounting and financial management processes. This study was conducted using qualitative methods and using data collection techniques through interviews to understand in depth the process of preparing invoice-based financial reports at PT. ABC. This approach was chosen because it allows researchers to dig up information in detail and understand the context and dynamics in the financial reporting system. PT. ABC, a private company engaged in the field of CNG (Compressed Natural Gas) Supplier, requires an effective system to manage and organize financial data related to sales and expenditure transactions.